RESEARCH OF THE PULSE PARAMETERS OF A DEFORMATION WAVE AT SURFACE-PLASTIC STRENGTHENING (World Science, 2022)
The article considers the issue of increasing the efficiency of shock energy and recording equipment for the study of the parameters of the deformation wave pulse. The review of the last researches and publications is carried out and perspective directions at designing of the special measuring equipment are established. A method is proposed and an experimental-measuring complex for the study of the momentum parameters in the deformation zone under different initial conditions is developed. The study of the parameters, of the shock pulse and micro hardness, of the strengthened material in the deformation zone using different versions, of the impact systems. It is established that when using a shock system with a step-shaped striker, the shock wave is characterized by a complex shape of the pulse. To assess the reliability of the obtained results, a test problem was solved in the environment of the Abaqus software package. When designing new technological processes of strengthening, the results of experimental studies such as the impact system and the parameters and modes of the processing process are of particular importance. It is established that the best result is shown by shock systems, which allow forming a prolonged shock pulse.